2022
DOI: 10.1097/cm9.0000000000002408
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative dexmedetomidine administration does not reduce the risk of acute kidney injury after non-cardiac surgery: a meta-analysis

Abstract: Background: Post-operative acute kidney injury (AKI) is one of the most common and serious complications after major surgery and is significantly associated with increased risks of morbidity and mortality. This meta-analysis was conducted to evaluate the effects of perioperative dexmedetomidine (Dex) administration on the occurrence of AKI and the outcomes of recovery after noncardiac surgery. Methods: The PubMed, Embase, Web of Science, and Cochrane Library databases were systematically searched for studies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…However, certain limitations must be acknowledged, including the fact that the duration of hypertension is not known and that there may be variability in the medications used to treat hypertension, potentially impacting the analysis. In our study, the incidence of AKI was 7.66%, similar to the findings recently reported by Kork et retrospective study of 39369 surgical patients using KDIGO diagnostic criteria, the incidence of AKI was 6%) (Kork et al, A recent meta-analysis showed that perioperative dexmedetomidine administration was not associated with postoperative AKI risk (Hu et al, 2022); however, the did not specifically focus on hypertensive patients who were at a higher postoperative AKI risk. In contrast, our study examined hypertensive patients and identified that dexmedetomidine administration was associated with a reduced postoperative AKI risk in hypertensive patients undergoing non-cardiac surgery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, certain limitations must be acknowledged, including the fact that the duration of hypertension is not known and that there may be variability in the medications used to treat hypertension, potentially impacting the analysis. In our study, the incidence of AKI was 7.66%, similar to the findings recently reported by Kork et retrospective study of 39369 surgical patients using KDIGO diagnostic criteria, the incidence of AKI was 6%) (Kork et al, A recent meta-analysis showed that perioperative dexmedetomidine administration was not associated with postoperative AKI risk (Hu et al, 2022); however, the did not specifically focus on hypertensive patients who were at a higher postoperative AKI risk. In contrast, our study examined hypertensive patients and identified that dexmedetomidine administration was associated with a reduced postoperative AKI risk in hypertensive patients undergoing non-cardiac surgery.…”
Section: Discussionsupporting
confidence: 89%
“…A recent meta-analysis showed that perioperative dexmedetomidine administration was not associated with postoperative AKI risk ( Hu et al, 2022 ); however, the study did not specifically focus on hypertensive patients who were at a higher postoperative AKI risk. In contrast, our study examined hypertensive patients and identified that dexmedetomidine administration was associated with a reduced postoperative AKI risk in hypertensive patients undergoing non-cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published in 2021 suggested that dexmedetomidine may have renoprotective effects, but this study mixed cardiac and non-cardiac procedures in both adult and pediatric patients [41]. Another study by Hu, et al included four RCTs and two retrospective studies to show that dexmedetomidine did not reduce the rate of AKI after non-cardiac surgery [8]; however, the results were limited by a small number of trials, low quality of evidence, and lack of renal function parameters. Abuelazm and colleagues performed a meta-analysis evaluating the impact of dexmedetomidine on renal outcomes in kidney transplantation only, without other types of surgery [42].…”
Section: Discussionmentioning
confidence: 94%
“…benefits have yet to be validated in non-cardiac surgery. Recently, a meta-analysis involving six studies suggested that dexmedetomidine did not alter the risk of AKI after non-cardiac surgery [8]. Nevertheless, their study mixed both randomised controlled trials (RCTs) and retrospective cohorts and did not include the recently published studies that reported the AKI outcome [9,10].…”
mentioning
confidence: 99%
“…However, there is ongoing debate related to the efficiency of dexmedetomidine in AKI prevention. A new meta-analysis and two high-quality RCTs reported no significant influence of dexmedetomidine on the AKI incidence (45). Therefore, after conducting a systematic search, we performed this meta-analysis that included 25 RCTs.…”
Section: Discussionmentioning
confidence: 99%